Eyes on Media Framing: Study of the Representation on COVID-19 Vaccine News - Rahardini, Nimas Ayu (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This research aims to find out how media represent the vaccine news during pandemic. This is related to the use of intensifiers as a measure of the degree of neutrality of news writers. This research is qualitative research supported by the quantification method. The data used is online news about the covid-19 vaccination in January - July 2021. A total of 43.288 words token has been collected online. This research is a corpus-based critical discourse analysis research. Three-Dimensional model by Fairclough is the theory used and applied in this research. The results show that news has the power to control the interpretation of readers and has a direct impact on social conditions. Several strategies were used by the covid-19 vaccination news writers, including the use of amplification (+intensifiers), the use of adjective collocations, and also the use of booster intensifiers. Intensifiers are mostly used to highlight the quality and enhancement of the covid-19 vaccination. This is relevant to the current condition that people are enthusiastic about vaccination programs as a result of media framing, especially news.